Estuarine-dependency and multiple habitat use by dusky kob Argyrosomus Japonicus (Pisces: Sciaenidae) - Childs, Amber-Robyn (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2013)
Dusky kob Argyrosomus japonicus is a wide-ranging estuarine-dependent Sciaenid and an important fishery species throughout most of its distribution. It is one of South Africa's most valuable coastal fishery species. High levels of juvenile exploitation in estuaries and ineffective management regulations have led to stock collapse, highlighting the need to better understand the spatial and temporal aspects of estuarine-dependency and multiple habitat use. Habitat connectivity is a critical property of estuarine-associated fishes and it therefore follows that knowledge of this link is fundamental in understanding population dynamics and the nursery role of estuarine and/or marine habitats. While dusky kob occur in both estuaries and nearshore coastal zones, limited information on connectivity among these habitats exists. The aim of this study is to assess the role of estuarine nursery habitats in the life cycle of the dusky kob by examining multiple habitat connectivity and determining the drivers associated with estuarine use. A total of 96 dusky kob (237"“1280 mm total length) were tagged with acoustic transmitters in both the estuarine and marine environments of Algoa Bay, Eastern Cape, South Africa between May 2008 and September 2010. Their movements were monitored using a network of automated data-logging acoustic receivers deployed in the Sundays Estuary, seven neighbouring estuarine habitats, two commercial harbours and various sites within Algoa Bay. And more...
Keywords: Argyrosomus -- Habitat -- South Africa -- Algoa Bay; Argyrosomus -- Behavior -- South Africa -- Algoa Bay; Argyrosomus -- Migration -- South Africa -- Algoa Bay; Estuarine fishes -- South Africa -- Algoa Bay; Habitat selection -- South Africa -- Algoa Bay; Argyrosomus -- South Africa -- Sundays Estuary (Eastern Cape); Underwater acoustic telemetry